SISTEM KONTROL ATAP RUMAH BERBASIS ANDROID DENGAN MIKROKONTROLLER ARDUINO UNO: Atap otomatis - Nurul Khairani; Yono Cahyono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A control system for opening and closing the roof of a house is very likely needed for today's millennial society. In addition to convenience, this system is very useful for improving air circulation in the house, getting direct sunlight which can be used for drying and there are many other advantages that will be needed later. As we know that building an open room requires land that cannot be used under certain conditions or weather, such as a drying area which cannot be used when it is raining, so a roof control system that can be opened and closed is very efficient for solving problems in the room. open. The best solution for building an open roof is with an automatic roof system using a microcontroller. The microcontroller system using Arduino Uno is very helpful as an automation system for controlling the opening and closing of the roof of the house, so that it can help control the roof of the house without problems. Coupled with a remote control system and weather detection sensors that will make the control process easier. BlackBox Testing was carried out on the Blynk application that was created and connected to the ESP8266 to produce an output that is valid and can be connected to the microcontroller, as well as sensor functions that run and detect weather accurately. With the existence of a roof control system with a microcontroller, it is hoped that it can create more useful home functions.